Separating organochlorine pesticides by high performance liquid chromatography. A technical note - Bauza, R.; Subero, N.; Ysambertt, F.; Márquez, N. (Rev. Téc. Fac. Ing. Univ. Zulia)
Nitrile and silica phases were tested as column packing for normal phase liquid chromatographic separations of organochlorine pesticides in mobile phase consisting of n-heptane. Excellent separation for the pp’-DDD, op’-DDD (isomers), op’-DDT and pp’-DDT (isomers) was achieved using a nitrile column, but no isomer separation was attained using a silica column. Evaluation of the chromatographic parameters (a=selectivity, R=resolution, N=theoretical plate number, and k’=capacity factor) was performed for each column.